Exploring Black Soldier Fly Frass as Novel Fertilizer for Improved Growth, Yield, and Nitrogen Use Efficiency of Maize Under Field Conditions - Beesigamukama, Dennis; Mochoge, Benson; Korir, Nicholas K.; Fiaboe, Komi K. M.; Nakimbugwe, Dorothy; Khamis, Fathiya M.; Subramanian, Sevgan; Dubois, Thomas; Musyoka, Martha W.; Ekesi, Sunday; Kelemu, Segenet; Tanga, Chrysantus M. (Frontiers in Plant Science, 2020)
Black soldier fly frass fertilizer (BSFFF) is increasingly gaining momentum worldwide as organic fertilizer. However, research on its performance on crop production remains largely unknown. Here, we evaluate the comparative performance of BSFFF and commercial organic fertilizer (SAFI) on maize (H513) production. Both fertilizers were applied at the rates of 0, 2.5, 5 and 7.5 t ha-1, and 0, 30, 60 and 100 kg nitrogen (N) ha-1. Mineral fertilizer (urea) was also applied at 0, 30, 60 and 100 kg N ha-1 to establish the N fertilizer equivalence (NFE) of the organic fertilizers. Maize grown in plots treated with BSFFF had the tallest plants and highest chlorophyll contents. Plots treated with 7.5 t ha-1 of BSFFF had 14% higher grain yields than plots treated with a similar rate of SAFI. There was a 27% and 7% increase in grain yields in plots treated with 100 kg N ha-1 of BSFFF compared to those treated with equivalent rates of SAFI and urea fertilizers, respectively. Application of BSFFF at 7.5 t ha-1 significantly increased N uptake by up to 23% compared to the equivalent rate of SAFI. Likewise, application of BSFFF at 100 kg N ha-1 increased maize N uptake by 76% and 29% compared to SAFI and urea, respectively. Maize treated with BSFFF at 2.5 t ha-1 and 30 kg N ha-1 had higher nitrogen recovery efficiencies compared to equivalent rates of SAFI. The agronomic N use efficiency (AEN) of maize treated with 2.5 t ha-1 of BSFFF was 2.4 times higher than the value achieved using an equivalent rate of SAFI. Also, the AEN of maize grown using 30 kg N ha-1 was 27% and 116% higher than the values obtained using equivalent rates of SAFI and urea fertilizers, respectively. The NFE of BSFFF (108%) was 2.5 times higher than that of SAFI. Application rates of 2.5 t ha-1 and 30 kg N ha-1 of BSFFF were found to be effective in improving maize yield, while double rates of SAFI were required. Our findings demonstrate that BSFFF is a promising and sustainable alternative to commercial fertilizers for increased maize production.